Misinformation Inoculation and Literacy Support Tweetorials on COVID-19. (January 2021) - Graham, S. Scott
Many expected federal public health agencies to provide timely and accurate information about the COVID-19 pandemic. That did not happen. In response, physicians and epidemiologists have explored new ways to educate the public about COVID-19 and protect against misinformation. One genre that has received significant uptake is the tweetorial, threaded tweets that educate followers on technical matters. This article builds on prior genre studies of the tweetorial to explore how #MedTwitter and #EpiTwitter communities have refashioned the emerging conventions of the tweetorial as part of efforts to protect the public from COVID-19 misinformation.